Prussian blue electrode material, potassium ion battery and preparation method thereof

By adding silicone additives to the organic electrolyte, the problem of introducing crystallization water in the preparation process of Prussian blue electrode materials is solved, and its cycle stability and electrochemical performance is improved. It is suitable for large-scale industrial production and improves potassium Electrochemical properties of ion batteries.

CN119481038APending Publication Date: 2025-02-18SHANGHAI UNIV OF ENG SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411536981.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the preparation process, crystallization water is easily introduced in Prussian blue electrode materials, which affects its structural stability and electrochemical properties. In addition, the existing technology has little research on the electrolytes that are suitable for it, which affects the commercial application of potassium ion batteries.

Method used

Add silicone additives to the organic electrolyte to alleviate interfacial side reactions, remove harmful H2O and HF, reduce the accumulation of by-product KF, and improve the cycle stability of Prussian blue electrode materials.

Benefits of technology

It effectively improves the cyclic stability and electrochemical performance of Prussian blue electrode materials, extends its specific capacity attenuation time, is suitable for large-scale industrial production, and improves the overall electrochemical performance of potassium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481038A_ABST
    Figure CN119481038A_ABST
Patent Text Reader

Abstract

The invention discloses a Prussian blue electrode material, a potassium ion battery and a preparation method thereof.The preparation method comprises the steps that transition metal salt is dissolved in a solvent, a chelating agent and ascorbic acid are added, the mixture is violently stirred and dissolved, and a solution A is obtained; dissolving potassium ferrocyanide and potassium citrate in deionized water to obtain a solution B; slowly dropwise adding the solution A into the solution B under the conditions of normal temperature and continuous stirring for co-precipitation reaction, shading, standing and aging a product, centrifuging, washing and drying in vacuum to obtain a Prussian blue positive electrode material, uniformly mixing the Prussian blue positive electrode material with conductive black and a binder in proportion, grinding into slurry, coating a carbon-coated aluminum foil with the slurry to obtain a positive electrode plate, taking a potassium plate with the diameter phi of 14mm as a negative electrode, and taking a negative electrode plate with the diameter phi of 14mm as a negative electrode; 0.5%-5% of an additive is added into the organic electrolyte, and the potassium ion battery is assembled under the protection of filled argon. By adding the additive, the interface side reaction is effectively reduced, a relatively stable crystal structure is maintained, the cycling stability of the material is improved, and the electrochemical performance of the potassium ion battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage, and in particular relates to a Prussian blue electrode material, a potassium ion battery and a preparation method thereof. Background Art

[0002] In recent years, the efficient storage and utilization of renewable clean energy such as tidal energy, solar energy, and wind energy is crucial. In this context, electrochemical energy storage technology has proven to be an efficient, environmentally friendly, and easy-to-integrate solution that can provide a reliable power supply. In the past three decades, lithium-ion batteries have dominated the electrochemical energy storage market with their high energy density and have achieved remarkable success in fields such as communications, electric vehicles, and grid energy storage. However, the shortage of natural lithium and the unpredictable fluctuations in lithium and transition metal prices have made lithium-ion batteries face challenges in large-scale energy storage applications.

[0003] Potassium-ion batteries have become a potential alternative to lithium-ion batteries due to their abundant potassium sources, low cost, high energy efficiency and safety. Among the positive electrode materials for potassium-ion batteries, Prussian blue has attracted extensive attention from researchers due to its advantages such as high theoretical specific capacity, open framework structure and relatively simple synthesis method. It is a promising positive electrode material for potassium-ion batteries that is easy to industrialize. However, the material structure will inevitably introduce a lot of crystal water during the preparation process, which seriously affects its structural stability and thus affects the electrochemical performance of the battery.

[0004] At present, most of the research focuses on the synthesis and modification of Prussian blue materials, while relatively few studies are conducted on electrolytes suitable for Prussian blue. Developing suitable electrolytes for Prussian blue materials to maximize their working performance is a key link in the commercialization of potassium ion batteries. Summary of the invention

[0005] The main purpose of the present invention is to provide a Prussian blue electrode material, adding a siloxane additive to an organic electrolyte, effectively reducing the interface side reaction, removing harmful H2O and HF in the organic electrolyte, reducing the accumulation of the byproduct KF, improving the cycle stability of the material, and solving the problem of many byproducts on the surface of the Prussian blue electrode sheet and the rapid attenuation of the material specific capacity. In addition, the raw material price is low, and the synthesis modification process is simple and easy compared to the Prussian blue material, which is suitable for large-scale industrial production.

[0006] Another object of the present invention is to provide a positive electrode sheet comprising the above-mentioned Prussian blue electrode material.

[0007] Another object of the present invention is to provide a potassium ion battery, in which an organic electrolyte additive is added to an organic electrolyte to effectively reduce the interface side reaction, remove harmful H2O and HF in the organic electrolyte, reduce the accumulation of the byproduct KF, improve the cycle stability of the material, and have a good improvement effect on the electrochemical performance of the potassium ion battery.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] The present invention provides a Prussian blue electrode material, which is prepared by a preparation method comprising the following steps:

[0010] (1) dissolving a transition metal salt in a solvent, adding a chelating agent and ascorbic acid, and vigorously stirring to dissolve, to obtain a solution A;

[0011] (2) dissolving potassium ferrocyanide and potassium citrate in deionized water to obtain solution B;

[0012] (3) slowly adding solution A to solution B at room temperature and under continuous stirring using a peristaltic pump to perform a coprecipitation reaction, and continuing to stir after the addition is completed;

[0013] (4) The product obtained in step (3) is shielded from light, allowed to stand for aging, centrifuged, washed, and vacuum dried to obtain a Prussian blue positive electrode material.

[0014] Preferably, in step (1), the transition metal salt is selected from one or more of nitrate, sulfate, acetate and hydrochloride;

[0015] and / or the solvent is deionized water;

[0016] And / or the chelating agent is selected from one or more of potassium citrate, potassium pyrophosphate, and dipotassium ethylenediaminetetraacetate.

[0017] More preferably, in step (1), the transition metal salt is selected from sulfate, selected from one or more of iron sulfate, nickel sulfate, manganese sulfate, and cobalt sulfate; the solvent is deionized water; and the chelating agent is potassium citrate.

[0018] Preferably, in step (2), the molar ratio of potassium ferrocyanide to potassium citrate is 4:5.

[0019] Preferably, in step (3), the light-shielding and static aging time is 24 hours, the washing is performed by washing with deionized water and anhydrous ethanol three times each; the vacuum drying temperature is 120° C. and the time is 12 hours.

[0020] The present invention also provides a positive electrode sheet, comprising the above-mentioned Prussian blue positive electrode material, and the preparation method comprises: the Prussian blue positive electrode material, conductive black and binder are mixed evenly in proportion, then N-methylpyrrolidone is added and ground into slurry, which is coated on carbon-coated aluminum foil with a thickness of 200 μm, and vacuum dried at 120° C. for 12 hours to obtain the obtained slurry.

[0021] Preferably, the binder is polyvinylidene fluoride, the conductive black is conductive black Super P, and the mass ratio of the Prussian blue positive electrode material, conductive black and the binder is 7:2:1.

[0022] The present invention also provides a potassium ion battery, which comprises the positive electrode sheet.

[0023] The present invention also provides a method for preparing the potassium ion battery, comprising: cutting the positive electrode sheet into The disc is used as the positive electrode. The potassium sheet is used as the negative electrode, the glass fiber separator is Whatman GF-A, 1M KPF6 is dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1) + 5% fluoroethylene carbonate (FEC) as the organic electrolyte, and organic electrolyte additives are added, and it is assembled under the protection of argon gas.

[0024] Preferably, the organic electrolyte additive is selected from one or more of (3-aminopropyl)triethoxysilane (APTS), N-(trimethylsilyl)acetamide, N-methyl-N-(trimethylsilyl)trifluoroacetamide, and the added amount accounts for 0.5% to 5% of the mass of the organic electrolyte.

[0025] More preferably, the organic electrolyte additive is (3-aminopropyl)triethoxysilane, and the added amount accounts for 1% of the mass of the organic electrolyte.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention adopts a simple coprecipitation method to synthesize the Prussian blue cathode material with the assistance of potassium citrate, adds additives to the organic electrolyte, effectively reduces the interface side reaction, removes the crystal water released during the Prussian blue cycle, prevents the decomposition of H2O to produce gas under high voltage, and avoids the entry of larger hydrated potassium ions into the material to destroy the crystal structure, greatly improving the cycle stability of the Prussian blue cathode material in the potassium ion battery, thereby solving the problem of many byproducts on the surface of the Prussian blue electrode sheet and the rapid attenuation of the material specific capacity. In addition, the raw material price is low, and the synthesis and modification process is simple and easy relative to the Prussian blue material, which is suitable for large-scale industrial production.

[0028] 2. In the potassium ion battery of the present invention, the addition of the additive effectively reduces the interface side reaction, maintains a relatively stable crystal structure, removes harmful H2O and HF in the organic electrolyte, reduces the accumulation of the byproduct KF, improves the cycle stability of the material, and has a good improvement effect on the electrochemical performance of the potassium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The button cells prepared with different amounts of electrolyte additives in Example 1 were -1 Cyclic curve of 800 cycles at a current density of .

[0030] Figure 2 The button cell prepared before and after adding the electrolyte additive in Example 2 at 200 mAg -1 Cyclic curve of 500 cycles at a current density of .

[0031] Figure 3 The button cell in Example 2 is 200 mAg -1 Impedance diagram after 500 cycles at a current density of . Specific embodiments

[0032] The embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art without any creative work are all within the scope of protection of this patent.

[0033] In order to describe the present invention more clearly, the Prussian blue electrode material, potassium ion battery and preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments.

[0034] Example 1

[0035] Weigh 20 mmol of ferric sulfate, nickel sulfate, and cobalt sulfate in a molar ratio of 1:1:1 and dissolve them in 250 mL of deionized water. Add 50 mmol of potassium citrate and 2 g of ascorbic acid and stir vigorously to dissolve to obtain solution A. Dissolve 40 mmol of potassium ferrocyanide and 50 mmol of potassium citrate in 250 mL of deionized water to obtain solution B. Use a peristaltic pump to slowly drop solution A into solution B and stir continuously. Continue stirring for 12 hours after the addition is completed. Then, shade and let stand for 24 hours, collect the precipitate by centrifugation, wash it 3 times with deionized water and anhydrous ethanol each, and dry it in vacuum at 120°C for 12 hours. The synthesized material is named NiFeCo-PBA.

[0036] The prepared NiFeCo-PBA material, conductive black (Super P) and binder (PVDF) were evenly mixed in a mass ratio of 7:2:1, and then the solvent N-methylpyrrolidone (NMP) was added to grind into slurry, coated on carbon-coated aluminum foil with a thickness of 200 μm, and placed in a vacuum oven at 120°C for 12 h to obtain an electrode sheet.

[0037] Cut the prepared electrode sheets into of discs, with The potassium sheet was used as the negative electrode, the glass fiber separator was whatman GF-A, and 1M KPF6+EC / DEC (V=1:1)+5% FEC was used as the electrolyte. 0wt%, 0.5wt%, 1wt%, and 1.5wt% of (3-aminopropyl)triethoxysilane additives were added respectively. The button cells were assembled in an argon-filled glove box, and the electrochemical properties were tested using the LAND test system.

[0038] Table 1 shows the NiFeCo-PBA Prussian blue electrode material prepared in Example 1 at 100 mAg under different amounts of electrolyte additives. -1 Cycling performance at current density.

[0039] Table 1

[0040]

[0041] From Table 1 and Figure 1 It can be seen that when 1.0 wt% (3-aminopropyl) triethoxysilane additive is added, the Prussian blue cathode material battery with this ratio of additive has the highest specific capacity after 800 cycles, which is 84.3 mAh g -1 The capacity retention rate is 66.8%, which is 13% higher than that of batteries without additives.

[0042] Example 2

[0043] Weigh 20 mmol of ferric sulfate, nickel sulfate, and manganese sulfate in a molar ratio of 7:2:1 and dissolve them in 250 mL of deionized water. Add 50 mmol of potassium citrate and 2 g of ascorbic acid and stir vigorously to dissolve to obtain solution A. Dissolve 40 mmol of potassium ferrocyanide and 50 mmol of potassium citrate in 250 mL of deionized water to obtain solution B. Use a peristaltic pump to slowly drop A into B and stir continuously. Continue stirring for 12 hours after the addition is completed. Then, shade it and let it stand for 24 hours. Collect the precipitate by centrifugation, wash it 3 times with deionized water and anhydrous ethanol each, and dry it in vacuum at 120°C for 12 hours. The synthesized material is named NiFeMn-PBA.

[0044] The prepared NiFeMn-PBA, Super P and PVDF were evenly mixed in a mass ratio of 7:2:1, then NMP was added and ground into slurry, which was coated on carbon-coated aluminum foil with a thickness of 200 μm, and placed in a vacuum oven and baked at 120° C. for 12 h to obtain an electrode sheet.

[0045] Cut the prepared electrode sheets into of discs, with The potassium sheet was used as the negative electrode, the glass fiber separator was made of Whatman GF-A, and the electrolyte was 1M KPF6+EC / DEC (V=1:1)+5% FEC. 0wt% and 1wt% of (3-aminopropyl)triethoxysilane additives were added respectively. The button cells were assembled in an argon-filled glove box, and the electrochemical performance tests were carried out using the LAND test system and Chenhua electrochemical workstation.

[0046] Figure 2 The button cell prepared before and after adding the electrolyte additive in Example 2 at 200 mAg -1 The cycle curve of 500 cycles at a current density of . It can be seen that the battery without additives has a specific capacity of 73.9 mAh g after 500 cycles. -1 The capacity retention rate is 64.8%, while the battery with 1wt% APTS has a remaining capacity of 87.5mAh g -1 The capacity retention rate is 76.1%, an increase of 11.3%. After using APTS electrolyte additive, the cycle stability of Prussian blue is significantly improved.

[0047] Figure 3 The button cell in Example 2 is 200 mAg -1 Impedance diagram after 500 cycles at a current density of . Since APTS reacts with HF in the electrolyte, the HF content is reduced, the continuous accumulation of the byproduct KF is prevented, and the K + After adding additives, the impedance of the battery is significantly smaller for the same number of cycles, which significantly improves the electrochemical performance of potassium ion batteries.

[0048] The difference between Examples 3 to 7 and Examples 1 and 2 is that the types of Prussian blue electrode materials are different. -1 The performance is shown in Table 2 after 100 cycles at a current density of .

[0049] Table 2

[0050]

[0051] As shown in Table 2, in combination with Examples 1 to 7, the addition of 1 wt % APTS improves the cycle stability of all Prussian blue materials, but the degree of improvement is different, which is mainly determined by the properties of the material itself. At the same time, it proves that the additive has a significant improvement effect on the cycle of Prussian blue positive electrode materials.

[0052] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the protection scope of the present invention.

Claims

1. A Prussian blue electrode material, characterized in that: Prepared by a preparation method comprising the following steps: (1) dissolving a transition metal salt in a solvent, adding a chelating agent and ascorbic acid, and vigorously stirring to dissolve, to obtain a solution A; (2) dissolving potassium ferrocyanide and potassium citrate in deionized water to obtain solution B; (3) slowly adding solution A to solution B at room temperature and under continuous stirring using a peristaltic pump to perform a coprecipitation reaction, and continuing to stir after the addition is completed; (4) The product obtained in step (3) is shielded from light, allowed to stand for aging, centrifuged, washed, and vacuum dried to obtain the product.

2. The Prussian blue electrode material according to claim 1, characterized in that In step (1), the transition metal salt is selected from one or more of nitrate, sulfate, acetate and hydrochloride; and / or the solvent is deionized water; And / or the chelating agent is selected from one or more of potassium citrate, potassium pyrophosphate, and dipotassium ethylenediaminetetraacetate.

3. The Prussian blue electrode material according to claim 2, characterized in that In step (1), the transition metal salt is selected from sulfate, selected from one or more of iron sulfate, nickel sulfate, manganese sulfate, and cobalt sulfate; The solvent is deionized water; The chelating agent is potassium citrate.

4. The Prussian blue electrode material according to claim 1, characterized in that In step (2), the molar ratio of potassium ferrocyanide to potassium citrate is 4:

5.

5. The Prussian blue electrode material according to claim 1, characterized in that In step (3), the shading and aging time is 24 hours; The washing is performed by washing with deionized water and anhydrous ethanol 3 times each; The vacuum drying was carried out at a temperature of 120° C. and for a period of 12 h.

6. A positive electrode sheet, characterized in that: A Prussian blue positive electrode material comprising any one of claims 1 to 5; The preparation method of the positive electrode sheet comprises: mixing the Prussian blue positive electrode material, conductive black and binder in proportion, then adding N-methylpyrrolidone and grinding into slurry, coating on carbon-coated aluminum foil with a thickness of 200 μm, and vacuum drying at 120° C. for 12 hours to obtain the obtained slurry.

7. The positive electrode sheet according to claim 6, characterized in that: The binder is polyvinylidene fluoride; The conductive black is conductive black Super P; The mass ratio of the Prussian blue positive electrode material, the conductive black and the binder is 7:2:

1.

8. A potassium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 7.

9. The method for preparing a potassium ion battery according to claim 8, characterized in that: include: The positive electrode sheet is cut into a φ12mm disc as the positive electrode, a φ14mm potassium sheet is used as the negative electrode, a Whatman GF-A glass fiber separator, 1MKPF6+ethylene carbonate and diethyl carbonate (volume ratio 1:1)+5% fluoroethylene carbonate as the organic electrolyte, and 0.5% to 5% of the organic electrolyte additive is added, and the mixture is assembled under the protection of argon gas; The organic electrolyte additive is selected from one or more of (3-aminopropyl)triethoxysilane, N-(trimethylsilyl)acetamide, N-methyl-N-(trimethylsilyl)trifluoroacetamide, and the added amount accounts for 0.5% to 5% of the mass of the organic electrolyte.

10. The method for preparing a potassium ion battery according to claim 9, characterized in that: The organic electrolyte additive is (3-aminopropyl)triethoxysilane, and the added amount accounts for 1% of the mass of the organic electrolyte.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and lithium ion battery prepared therefrom

    CN108306048A

  • Polyorganic matter modified core-shell structure Prussian blue potassium ion battery positive electrode material and preparation method thereof

    CN113206224A

  • Prussian blue as well as preparation method and application thereof

    CN113540445A

  • High-entropy Prussian blue potassium ion battery positive electrode material, potassium ion battery and preparation method of high-entropy Prussian blue potassium ion battery positive electrode material

    CN115882045A

  • Nonaqueous electrolyte secondary battery

    JP2002042864A